MEMBEDAH KEPEMIMPINAN YOSUA DI ERA DISRUPSI: SEBUAH TELAAH KEPEMIMPINAN MENURUT BUKU LEADERSHIP EXCELLENCE KARYA PAT WILLIAMS - Feri Aman Mendrofa; Antonius Natan; Herbin Simanjuntak; Randy Marimbunna (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
The disruption era is an era human life is rapidly changing and evolving. Technological advancements have acted as catalysts for these changes and developments. Christian leadership is also not exempt from the demand for change. However, some churches and their leaders not ready to face significant changes in the disruption era. Leadership stagnation and the stronghold of traditions in the church are the principal causes. Yet, the changes in the disruption era are moving towards critical conditions that require Christian leaders to be vigilant. This anticipation is crucial because sometimes globalization and technological advancements can undermine spirituality. Therefore, the leadership paradigm is needed to keep Christianity as the salt and light of the world. To respond to this, in this article, the author uses the leadership of Joshua as a role model for leaders that should be emulate in the disruption era. Using a literature study method, the author conducted a series of activities to examine Joshua's leadership. Analyze the context and the meaning of words in interpreting texts related to Joshua's leadership. Analyzing the interpretation results through the theory of leadership in the book